From the Bosniak collection to the Central Library of the Bosniak national minority (Caprag department of the Vlado Gotovac Sisak Public Library) - Ivana Zorko (Bosniaca)
Aim: It is to show how, on the basis of several dozen books by Bosniak authors and titles that analyze topics from various areas of Islamic culture, science and art, a rich library emerged. Approach/methodology/design: The article is chronological – it tracks, from its early days, the changes in the collection, the space and the events, i.e., programs and activities. In its first part, the article describes the foundation of the Bosniak collection. The second part elaborates the development of the Bosniak library through establishing, acquiring and analyzing library material, as well as organizing programs and events. Results: The article displays the realization of the Bosniak Library’s main task, which is to carry out cultural activities purposed for the users of the Bosniak minority, the preservation and advancement of their national and cultural achievements, and cooperation with other communities, contributing to their active involvement into the cultural and public life of the city of Sisak. Practical use: The article can serve as a reminder and impetus for further quality work of the Bosniak Library, its recognition in other libraries in Croatia and beyond. Originality/value: This is the first article discussing the foundation and development of the Central Library of the Bosniak National Minority, opened with the support of the Ministry of Culture of the Republic of Croatia in 2012, as part of the Caprag branch of the Vlado Gotovac Sisak Public Library. The Library is one of ten central libraries of national minorities in the Republic of Croatia.